A method for the atmospheric correction of ENVISAT/MERIS data over land targets - Guanter, L; Gonzalez-Sanpedro, M; Moreno, J (2007)
An atmospheric correction algorithm for the retrieval of land surface reflectance from imagery acquired by the Medium Resolution Imaging Spectrometer (MERIS) on-board the European Space Agency (ESA) ENVIronmental SATellite (ENVISAT) platform has been implemented. The algorithm is designed to estimate the main atmospheric parameters needed in the correction, aerosol and water vapour contents, from the image itself, leading to an optimal characterization of the atmospheric state at the time of image acquisition. Once the atmospheric state has been defined, a second step deals with the retrieval of surface reflectance, accounting for the contribution of surface elevation and roughness as well as the atmospheric adjacency effect. The first part of this paper is devoted to the description of the method, outlining the main steps in the atmospheric characterization and in the subsequent surface reflectance retrieval. The validation task is detailed in the second part. Aerosol Optical Thickness (AOT) and water vapour content from different sites of the AErosol RObotic NETwork (AERONET) have been compared with the method's retrievals. Root Mean Square Errors (RMSEs) equal to 0.085, 0.065 and 0.048 are found for AOT at 440, 550 and 870 nm, respectively. Comparison with in situ measurements shows a satisfactory performance except for episodes of Saharan dust intrusions. For water vapour, a high correlation between MERIS and AERONET results is found, although the RMSE equals 0.316 g cm-2 due to a systematic overestimation when compared with AERONET data. It decreases to 0.098 when the retrievals are compared with the ESA water vapour level 2 product.